2011
DOI: 10.1007/s10278-011-9433-7
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Based Route-Definition System for Peripheral Bronchoscopy

Abstract: Multi-detector computed tomography (MDCT) scanners produce high-resolution images of the chest. Given a patient's MDCT scan, a physician can use an image-guided intervention system to first plan and later perform bronchoscopy to diagnostic sites situated deep in the lung periphery. An accurate definition of complete routes through the airway tree leading to the diagnostic sites, however, is vital for avoiding navigation errors during image-guided bronchoscopy. We present a system for the robust definition of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…We note in passing that deep peripheral sites can involve slight route adjustments prior to bronchoscopy, which can be noted during report inspection [38], [53]. In addition, there are known challenges in peripheral bronchoscopy in terms of effective tissue sampling, which arise beyond the efficacy of a guidance system.…”
Section: Discussionmentioning
confidence: 99%
“…We note in passing that deep peripheral sites can involve slight route adjustments prior to bronchoscopy, which can be noted during report inspection [38], [53]. In addition, there are known challenges in peripheral bronchoscopy in terms of effective tissue sampling, which arise beyond the efficacy of a guidance system.…”
Section: Discussionmentioning
confidence: 99%
“…We did not use our system during these phases of a patient procedure. As a standard practice, the physician reviewed the preplanned routes for each case before the start of bronchoscopy [16], [44], [45]. In addition, we recorded all procedures, including the VBN system’s GUI display, to assist with data analysis afterward.…”
Section: Resultsmentioning
confidence: 99%
“…Using the system, the physician previewed a “VB” by playing a cine movie of the VB view sequence suggested by the CT-derived route [16], [44], [45]. While this preview nominally illustrates the proper bronchoscope trajectory to execute during later live navigation, two issues remain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that image-based guidance significantly improves peripheral-lung biopsy performance over standard practice from 43% to 94% [9]. In addition, several other studies have shown that the system fits smoothly within the standard two-step lung cancer staging work flow [46], [50], [51], [68]. For example, we have applied the system to 30 patients who underwent peripheral bronchoscopy (age range: 18–85 years; 9 males, 21 females).…”
Section: Resultsmentioning
confidence: 99%